Modelling and stabilization of a three-axis ship-mounted mobile antenna system - KUSEYRİ, İBRAHİM SİNA (SAGE PUBLICATIONS LTD, 2017)
A mobile satellite communication antenna is a device installed on a moving carrier for mobile satellite communication. Gimballed motorized pedestals are used to eliminate the effect of disturbance and maintain uninterrupted communication when the carrier is moving. Mobile satellite communication antennas are becoming increasingly more popular due many advantages of mobile satellite communication. In this paper, a three-axis ship-mounted antenna on a pedestal gimbal system is studied. We study the problem with a different perspective and method from the previous work for two-axis antenna pedestals. The former studies treat the subsystems to be isolated and design controllers separately, which neglect the coupling effects in the dynamics of two or three-axis antenna pedestal gimbals. We treat three sub-systems as a whole and derive the dynamic model of the system using the Newton-Euler method. Based on the dynamic model, linear PI controllers are designed to stabilize the antenna to keep its orientation towards the satellite. The design objective of the control system is to direct the on-board antenna toward a satellite and to keep its orientation unaltered despite the effect of sea waves disturbing the antenna. Simulation results are presented to show the stabilization performance of the system with the synthesized controllers.
Keywords: Mobile antenna; stabilization; dynamic modeling; linear control; simulation; ROBUST ADAPTIVE-CONTROL